Transcriptomic Analyses of Scrippsiella trochoidea Reveals Processes Regulating Encystment and Dormancy in the Life Cycle of a Dinoflagellate, with a Particular Attention to the Role of Abscisic Acid - Deng, Yunyan; Hu, Zhangxi; Shang, Lixia; Peng, Quancai; Tang, Ying Zhong (Frontiers in Microbiology, 2017)
Due to the vital importance of resting cysts in the biology and ecology of many dinoflagellates, a transcriptomic investigation on Scrippsiella trochoidea was conducted with the aim to reveal the molecular processes and relevant functional genes regulating encystment and dormancy in dinoflagellates. We identified via RNA-seq 3,874 (out of 166,965575) differentially expressed unigenes (DEGs) between resting cysts and vegetative cells; a pause of photosynthesis (confirmed via direct measurement of photosynthetic efficiency); an active catabolism including β-oxidation, glycolysis, glyoxylate pathway, and TCA in resting cysts (tested via measurements of respiration rate); 12 DEGs encoding meiotic recombination proteins and members of MEI2-like family potentially involved in sexual reproduction and encystment; elevated expressions in genes encoding enzymes responding to pathogens (chitin deacetylase) and ROS stress in cysts; and 134 unigenes specifically expressed in cysts. We paid particular attention to genes pertaining to phytohormone signaling and identified 4 key genes regulating abscisic acid (ABA) biosynthesis and catabolism, with further characterization based on their full-length cDNA obtained via RACE-PCR. The qPCR results demonstrated elevated biosynthesis and repressed catabolism of ABA during the courses of encystment and cyst dormancy, which was significantly enhanced by lower temperature (4±1°C) and darkness. Direct measurements of ABA using UHPLC-MS/MS and ELISA in vegetative cells and cysts both fully supported qPCR results. These results collectively suggest a vital role of ABA in regulating encystment and maintenance of dormancy, akin to its function in seed dormancy of higher plants. Our results provided a critical advancement in understanding molecular processes in resting cysts of dinoflagellates.